Pengaruh Literasi Keuangan Digital dan Gaya Hidup terhadap Keputusan dalam Menggunakan Paylater pada Mahasiswa - Nenden Susilowati; Jovinka Nadya Epriella; Imam Rudi Mustofa; Rina Safitri; Yeremia Tobias Hutabarat (PPJP ULM, 2025)
The continuous progress in digital technology has brought about various modern financial services, one of which is paylater, a platform increasingly favored by university students. However, its utilization is largely influenced by students’ level of digital financial literacy and lifestyle preferences. This research seeks to examine the combined effect of digital financial literacy and lifestyle on students’ decisions to utilize paylater services within the Faculty of Economics and Business at Yogyakarta State University. The study adopted a quantitative method by administering online questionnaires to 72 active paylater users who were chosen using purposive sampling techniques. The gathered data were processed through multiple linear regression analysis. The results reveal that digital financial literacy (β = 0.350; p < 0.05) and lifestyle (β = 0.544; p < 0.05) significantly affect students’ decisions to use paylater. Jointly, these variables explain 67.4% of the variance in paylater usage decisions (R² = 0.674). The findings imply that students with higher digital financial literacy tend to make more rational and responsible financial choices, whereas those with a more consumptive lifestyle are more likely to use paylater services. Hence, enhancing digital financial literacy among students is essential to foster wiser and more sustainable financial behavior in the digital era.